Evaluación del daño producido por el complejo de lepidópteros plagas sobre nuez pecán (Carya illinoensis) en Tucumán, Argentina - Garat Herrera, María Gabriela; Caceres, Mauro; Carrizo, Beatriz Noemi (Universidad Nacional de La Plata, 2024)
Póster y Resumen